2023
DOI: 10.3991/ijim.v17i13.38439
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Saudi Female Student Learning Experiences in a Programming Subject Using Mobile Devices: An Empirical Study

Abstract: There is a dearth of research on how mobile learning might help Saudi female students in particular perform better in computer programming courses. This paper aims to measure educational experiences ofSaudi female students using an empirical study, based on aframework related to mobile learning in a computer programming subject. The empirical study sample involved 21 students who used the ViLLE software tool in their quizzes in programming class. This study includes a survey with a mixed-method approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Students using e-learning apps are 30% more likely to feel motivated and inspired to learn. The study results [20] showed that students were satisfied with their mobile learning experience. The level of satisfaction indicates how mobile devices can help students learn computer programming.…”
Section: Overviewmentioning
confidence: 82%
“…Students using e-learning apps are 30% more likely to feel motivated and inspired to learn. The study results [20] showed that students were satisfied with their mobile learning experience. The level of satisfaction indicates how mobile devices can help students learn computer programming.…”
Section: Overviewmentioning
confidence: 82%